Food Habits of Primary School students and Their Association with Body Mass Index. - Jamal SabrIdan; Jabbar Trish Ahmed; Hassan Faleeh Farhan (University of Thi-Qar Journal of Science, 2023)
food habits are a representation of the cumulative impacts of the foods that people eat, and they effectively explain how nutrition may influence overall results of wellness measurements. The overall purpose of the research is really to determine whether food habits and body composition are related amongst Al-Hilla city’s students in primary schools. Materials and methods: Cross-sectional descriptive study was done in Babylon Governorate (Al-Hilla District) in Iraq from 1st ofNovember 2021 to 1stof March 2022 on 384studentswho had been selected randomly and ranged in age from 6 to 13 years. The Body Mass Index (BMI)was calculated for students.Results: According to the results of the current study, 61% of individuals had normal BMI, 17% were obese, 16% were overweight, and 6% were underweight.BMI and gender have no statistically significant association.According to the survey, the majority of individuals (87%) possess neutral food patterns, while the minority (3%) has bad eating habits.Except for consuming snacks, the study have shownno significant connection between BMI and food patterns (P. value <0.001*). Conclusion:Most primary school students have neutral eating habits. Consumption of snacks and the educational level of the mother have been discovered to be significantly correlated with body weight.